PROGRAM IMPACT ANALYSIS CORPORATE SOCIAL RESPONSIBILITY(CSR) PT AWANA SAWIT LESTARI TOWARDS ECONOMIC EMPOWERMENT OF OIL PALM FARMING COMMUNITIES IN SARUDU VILLAGE, PASANGKAYU REGENCY - Fitriani, Fitriani; Syaifullah, Syaifullah; Asriyana, Asriyana (Economics Studies and Banking Journal (DEMAND), 2025)
Corporate Social Responsibility(CSR) is a concept that is increasingly gaining attention among companies, especially those operating in the natural resources sector. CSR not only functions as a form of corporate social responsibility, but also as a tool to accelerate local economic growth and empower communities. Currently, PT. Awana Sawit Lestari, which operates in Sarudu Village, Pasangkayu Regency, has implemented CSR programs since its establishment in 2019. These programs are designed to provide a positive contribution to the surrounding community, with a focus on economic empowerment, the environment, health, and education. The research method used in this study is a qualitative method. The data collection techniques are through observation, interviews, and documentation. This study uses data analysis techniques, namely data reduction, data presentation and data verification. Checking the validity of the data uses 4 triangulations, namely sources, methods, investigators and theories. The results of the study show that there is a real contribution in encouraging the economic empowerment of oil palm farmers around its operational area. Through a participatory approach and programs that focus on increasing capacity, strengthening farmer institutions, and providing production facilities, the company has succeeded in creating a positive impact that is not only short-term but also leads to long-term sustainability. Active community involvement in every stage of program implementation is one of the key factors for the success of this CSR. The community feels more appreciated and has a sense of ownership of the program being implemented. Supporting factors for the success of CSR implementation include support from community leaders and positive responses from residents, while inhibiting factors include lack of transparency and uneven community participation. In conclusion, the implementation of CSR by PT. Awana Sawit Lestari has had a positive impact on the community, but there needs to be improvement in the aspects of coordination and program expansion so that the results are more optimal and sustainable.